2013
DOI: 10.3389/fimmu.2013.00235
|View full text |Cite
|
Sign up to set email alerts
|

A Temporal Model of Human IgE and IgG Antibody Function

Abstract: The diversity of the human antibody repertoire that is generated by V(D)J gene rearrangement is extended by nine constant region genes that give antibodies their complex array of effector functions. The application of high throughput sequencing to the study of V(D)J gene rearrangements has led to significant recent advances in our understanding of the antigen-binding repertoire. In contrast, our understanding of antibody function has changed little, and mystery still surrounds the existence of four distinctive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
136
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(152 citation statements)
references
References 57 publications
9
136
1
6
Order By: Relevance
“…IgG3 has distinct roles from other IgG subclasses. It has a much higher turnover than the other subclasses with a half-life of 7 versus 21 days, it is the best activator of complement and, together with IgE, is the first of the subclasses to appear in an immune response [17]. Thus, IgG3 joins the IgM-dependent early defence to bind and clear foreign antigens.…”
Section: Discussionmentioning
confidence: 99%
“…IgG3 has distinct roles from other IgG subclasses. It has a much higher turnover than the other subclasses with a half-life of 7 versus 21 days, it is the best activator of complement and, together with IgE, is the first of the subclasses to appear in an immune response [17]. Thus, IgG3 joins the IgM-dependent early defence to bind and clear foreign antigens.…”
Section: Discussionmentioning
confidence: 99%
“…The precise role of the four IgG subclasses in the immune response is unclear. A recent temporal model suggests that the different properties of the IgG subclasses, their concentrations, and their emergence at different stages facilitate a more cohesive immune response (46). An understanding of the distinct properties of the IgG subclasses is desired; we now have complete scattering analyses for human IgG1 and IgG4.…”
Section: Discussionmentioning
confidence: 99%
“…The differential ratios of these three antibodies determine the pattern of immune response. Ig G4 is believed to appear late as a part of the humoral immune process, only on persistent antigenaemia, having a primary role in dampening down inflammation by helping to curtail FcR-mediated processes [6,7]. The circulating half-life of Ig G4 is 21 days.…”
Section: The Family Of Immunoglobulin-gmentioning
confidence: 99%
“…[4,5]. It has been suggested that IgG3 along with Ig E appears earliest in the immune response, followed by Ig G2 and G1 [6]. The differential ratios of these three antibodies determine the pattern of immune response.…”
Section: The Family Of Immunoglobulin-gmentioning
confidence: 99%